2017
DOI: 10.1080/14763141.2017.1353129
|View full text |Cite
|
Sign up to set email alerts
|

The validity and intra-tester reliability of markerless motion capture to analyse kinematics of the BMX Supercross gate start

Abstract: The aim of this study was to quantify the validity and intra-tester reliability of a novel method of kinematic measurement. The measurement target was the joint angles of an athlete performing a BMX Supercross (SX) gate start action through the first 1.2 s of movement in situ on a BMX SX ramp using a standard gate start procedure. The method employed GoPro® Hero 4 Silver (GoPro Inc., USA) cameras capturing data at 120 fps 720 p on a 'normal' lens setting. Kinovea 0.8.15 (Kinovea.org, France) was used for analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The results of this study showed that Kinovea is useful in the analysis of locomotor activity in mice, as shown in previous studies [13-20]. A computer software program for animal experiments must be purchased with video equipment, and used only by researchers with the equipment.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The results of this study showed that Kinovea is useful in the analysis of locomotor activity in mice, as shown in previous studies [13-20]. A computer software program for animal experiments must be purchased with video equipment, and used only by researchers with the equipment.…”
Section: Discussionsupporting
confidence: 58%
“…In recent years, the Kinovea software (version 0.8.24, http://www.kinovea.org) that tracks the movement of objects in videos has been released at no cost to the user. This software have already been used in other research fields [13-20], so it could be used in an effective analysis of locomotor acitivity. If this software has sufficient reliability and validity for analyzing locomotor activity, it will lead to reducing the budget of an animal experiment or using the same budget for other tests, which may promote research involving locomotor activity.…”
Section: Introductionmentioning
confidence: 99%
“…The present study used a validated biomechanical setup, introduced by Harvey et al 19 except for the motion analysis software. However, the motion analysis software was evaluated by Grigg et al 15 in a marker-less motion capture study that showed high intratester reliability and low absolute error in kinematic measurements. Another recent study demonstrated the validity and reliability of Kinovea as an accurate tool for optical tracking.…”
Section: Discussionmentioning
confidence: 99%
“…Xsens MVN [75]), and can already provide GRF and joint moment estimates during stereotypical activities such as walking [76,77]. To overcome discomfort and movement restriction issues associated with the use of multiple body-worn devices, markerless motion capture techniques are a non-invasive method for measuring different biomechanical variables in various sport environments [78,79,80,81,82,83]. These techniques may in the future allow for load metrics to be estimated at different levels.…”
Section: From Lab To Fieldmentioning
confidence: 99%